2017
DOI: 10.1177/0883911517690758
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of postoperative adhesions by biodegradable cryogels from pectin and chitosan polysaccharides

Abstract: The main complication that may arise after surgery is the formation of adhesions. The current trend in the prevention of postoperative adhesions is the application of anti-adhesive barrier materials for the separation of wound tissue during the critical period of mesothelial repair and healing. In this work, cryogels based on pectin and chitosan were obtained by the ionic cryotropic gelation method. It was found that the Heracleum L. pectin cryogels are more elastic (73 ± 6 kPa) than the apple pectin cryogels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Chitosan has been widely used in a variety of biomedical applications such as tissue engineering, drug delivery, and manufacturing of wound dressing due to its excellent mechanical properties and biocompatibility. 1,2 In general, chitosan has important biological properties such as biocompatibility, antifungal and antibacterial activity, wound healing ability, anticancerous properties, immunoenhancing effect, and tissue regeneration. 3 It has been shown that the antibacterial activity of chitosan is due to the presence of amine functions in its chains.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan has been widely used in a variety of biomedical applications such as tissue engineering, drug delivery, and manufacturing of wound dressing due to its excellent mechanical properties and biocompatibility. 1,2 In general, chitosan has important biological properties such as biocompatibility, antifungal and antibacterial activity, wound healing ability, anticancerous properties, immunoenhancing effect, and tissue regeneration. 3 It has been shown that the antibacterial activity of chitosan is due to the presence of amine functions in its chains.…”
Section: Introductionmentioning
confidence: 99%
“…Twelve barriers in the group were identified with successful animal studies 102 , 123–136 ; however, only Dextran 70 progressed to have a single successful human study ( de novo and laparoscopic surgery). Each of the 12 barriers reported were easy to apply 102 , 117 , 124 , 126 , 132 , 136 ; however, safety, cost-effectiveness, and levels of postoperative pain remain unknown for each barrier.…”
Section: Resultsmentioning
confidence: 99%
“…Alginate cryogel cross-linked with Ca 2+ [19] Ionic cryotropic gelation of pectin-chitosan [20] Freezing-thawing cycle PVA-gelatin cryogel; hydrogen bonding, formation of crystallites of PVA [21] Agarose cryogel, intramolecular and intermolecular hydrogen bonding [22] Chitosan cryogel, formation of crystallites composed of D-glucosamine and N-acetylglucosamine units [23,24] Chemical cross-linking Reaction between the functional groups of polymer and cross-linker or polymer-polymer Condensation of an amine with the carbonyl group, formation of Schiff bases; chitosan and gelatin cross-linked with glutaraldehyde.…”
Section: Ionic Interactionmentioning
confidence: 99%
“…Owing to their high anti-adhesive properties and biocompatibility, AP cryogels have been proposed for the development of a barrier material for use in surgery [ 93 ]. Chitosan/pectin cryogels were produced [ 20 , 80 , 93 ]. The cryogels were formed by both electrostatic polyelectrolyte interactions between pectin and chitosan and cross-linking of chitosan with GA [ 80 ].…”
Section: Biodegradable Cryogelsmentioning
confidence: 99%